A conceptual framework for the estimation of opportunity loss at the regional-sectoral level with an application to Greece - Vakalo, Emmanuel-George G.; Plessas, Demetrius J. (The Greek Review of Social Research, 1978)
[Δε διατίθεται περίληψη / no abstract available]